Heat-conducting composite material, preparation method thereof and cooling roller
By covering the thermally conductive composite material on the metal cooling roller, the problem of poor thermal conductivity of traditional metal cooling rollers is solved, better cooling effect and film adhesion are achieved, and the performance of the composite fluid collector is improved.
Patent Information
- Application Number
- CN202411621364.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-25
AI Technical Summary
Traditional metal cooling rollers have poor thermal conductivity in the evaporation process, resulting in poor cooling effect and poor film adhesion, affecting product quality.
The metal roller is coated with a thermally conductive composite material, including a composite material layer and a thermally conductive insulating layer. The composite material layer is composed of a thermally conductive ceramic nanomaterial and a core-shell structure thermally conductive material, and the thermally conductive insulating layer is composed of a polymer material and a thermally conductive ceramic nanomaterial.
The thermal conductivity and adhesion of the film are improved, the adhesion of the base film on the roller is enhanced, the risk of film decomposition during the evaporation process is reduced, and the performance of the composite fluid collection is improved.
Smart Images

Figure BDA0005135622960000061 
Figure BDA0005135622960000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of batteries, and in particular to a heat-conducting composite material and a preparation method thereof, and a cooling roller. Background Art
[0002] The composite current collector adopts a three-layer composite structure of "metal-polymer material-metal". It is a new type of composite material made of polymer materials such as PET / PP as the base film, and a metal layer is deposited on both sides of the base film using a vacuum coating process. Among them, the principle of vacuum evaporation is to first heat the metal or non-metal material so that its components are evaporated in the form of atomic groups or molecular groups and deposited on the surface of the substrate. Compared with magnetron sputtering, this vacuum evaporation method is faster and more efficient, but because the temperature required to heat the metal or non-metal material to form steam is relatively high, a large amount of heat radiation will be generated during the heating process, causing the surface temperature of the base film to rise sharply, which can easily cause deformation of the base film. Therefore, it is necessary to add appropriate cooling measures in the evaporation process.
[0003] At present, metal cooling rollers have been developed to cool the base film during the evaporation process. However, there is no adsorption effect between the traditional metal roller and the film. It only relies on roller tension, which makes the adsorption between the film and the cooling roller poor, and the thermal conductivity is poor, resulting in poor cooling effect, thus affecting the quality of the final product. In the prior art, a ceramic layer is set on the surface of the metal cooling drum to insulate its surface, and then the roller and the film are charged, and the adsorption effect between the film and the cooling drum is improved by electrostatic adsorption. However, due to the poor thermal conductivity of ceramics, it is still relatively difficult to improve the thermal conductivity of the coating while ensuring the insulation of the coating. Summary of the invention
[0004] In order to improve the problems of poor cooling effect and poor film adhesion of traditional cooling rollers, the present invention proposes a thermally conductive composite material and a preparation method thereof and a cooling roller. The above purpose can be achieved by the following technical solution implementation method:
[0005] A thermally conductive composite material, comprising:
[0006] A composite material layer, the composite material layer comprising a filler and a core-shell structure thermal conductive material;
[0007] The filler is made of thermally conductive ceramic nanomaterial; the core-shell structure thermally conductive material comprises a core layer and a shell layer bonded to the core layer; the core layer is made of a material with a thermal conductivity greater than 10W / m·K, and the shell layer is made of thermally conductive ceramic nanomaterial;
[0008] A heat-conducting insulating layer is covered on the composite material layer; the heat-conducting insulating layer comprises a polymer material and a heat-conducting ceramic nano material.
[0009] Optionally, the core layer is selected from at least one of gold, silver, copper, aluminum, and aluminum oxide;
[0010] Preferably, the core layer is spherical or irregularly spherical, and the average particle size of the core layer is 10-150 μm.
[0011] Optionally, the thermal conductivity of the thermally conductive ceramic nanomaterial in the composite material layer and the thermally conductive insulating layer is greater than 5 W / m·K;
[0012] Preferably, the thermally conductive ceramic nanomaterials in the composite material layer and the thermally conductive insulating layer are independently selected from at least one of boron nitride, silicon nitride, titanium nitride, titanium dioxide, silicon carbide, aluminum nitride and gallium nitride.
[0013] Optionally, the average particle size of the thermally conductive ceramic nanomaterial is 20-500 nm.
[0014] Optionally, the polymer material is selected from at least one of polyvinyl alcohol resin, polyvinylidene fluoride resin, vinyl acetate, acrylic resin, polyurethane, epoxy resin, silicone resin, and phenolic resin.
[0015] The method for preparing the thermally conductive composite material comprises the following steps:
[0016] Step 1) mixing the metal material as the core layer with the binder, then adding the cross-linking agent and the thermal conductive ceramic nanomaterial, and mixing them evenly to obtain the composite material layer coating;
[0017] Step 2) mixing the thermally conductive ceramic nanomaterial, the polymer, the cross-linking agent and the curing agent to obtain a thermally conductive insulating layer coating;
[0018] Step three) coating the composite material layer coating on the substrate, and forming a composite material layer after curing; coating the thermal conductive insulating layer coating on the surface of the composite material layer away from the substrate, and obtaining the thermal conductive composite material after curing.
[0019] Optionally, the binder is selected from one of hydroxy silicone oil and curable epoxy resin;
[0020] Optionally, the crosslinking agent is selected from one of diethylene glycol dimethacrylate, triallyl cyanurate, methyltrimethylsilane, cumene hydroperoxide, tetramethoxysiloxane and tetraethoxysilane;
[0021] Optionally, the curing agent is selected from one of aliphatic amines, aromatic amines, alicyclic amines, polyamides, acid anhydrides, and tertiary amines.
[0022] Optionally, in step 1), 60-80 parts by volume of metal material are mixed with 6-20 parts by volume of binder, cross-linker and 20-40 parts by volume of thermally conductive ceramic nanomaterial, and mixed evenly to obtain a composite material layer coating; the amount of cross-linker is 5-15% of the mass of the binder.
[0023] Optionally, in step 2), 10 parts by weight of thermally conductive ceramic nanomaterials, 20-80 parts by weight of polymers, 2-8 parts by weight of cross-linking agents and 5-20 parts by weight of curing agents are mixed to obtain a thermally conductive insulating layer coating.
[0024] A cooling roller, comprising a metal roller, the metal roller being coated with the above-mentioned heat-conducting composite material;
[0025] The composite material layer in the thermally conductive composite material is coated on the surface of the metal roller; and the thermally conductive insulating layer in the thermally conductive composite material is arranged on the surface of the composite material layer away from the surface of the metal roller.
[0026] Optionally, the thickness of the thermally conductive composite material is 30-200 μm, wherein the thickness of the thermally conductive insulating layer is 10-100 μm, and the thickness of the composite material layer is 20-100 μm.
[0027] The invention also proposes the use of the above-mentioned cooling roller in the preparation of a composite current collector.
[0028] A cooling roller is applied to a winding system of a vacuum evaporation chamber, and a conductive layer is deposited on a polymer base film by vacuum evaporation to form a composite current collector.
[0029] The technical solution of the present invention has the following advantages:
[0030] The ceramic layer provided by the present invention can be realized by simple physical coating and chemical cross-linking methods, which is easy to realize. The first layer of the shell-core structure material of the ceramic layer composite material is based on the metal phase spherical material, which can make the coating have higher fracture toughness, better hardness and corrosion resistance, and the outer layer is coated with nano ceramic thermal conductive material, which is equivalent to overlapping the nano ceramic thermal conductive material between the metal phase spherical materials, and a more efficient heat conduction channel can be constructed; after the spherical shell-core structure material coating is prepared, a thin layer of thermal conductive nano material coating is coated on the upper layer to form a double-layer composite material structure, and compared with the single-layer thermal conductive ceramic material, the thermal conductivity and insulation are improved.
[0031] After the insulating ceramic coating provided by the present invention is coated on the surface of the cooling metal roller, a dense ceramic coating can be prepared on the roller surface. This dense ceramic coating has good thermal conductivity and good adhesion to the film, increases the adhesion of the base film on the roller, and reduces the risk of film stripping during the evaporation process; at the same time, since nanomaterials with good thermal conductivity are added to the ceramic coating, it can help the base film to quickly cool down during the evaporation of metal aluminum, reduce the risk of film deformation, and thus improve the performance of the composite current collector. DETAILED DESCRIPTION
[0032] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0033] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0034] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0035] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0036] The present invention provides a thermally conductive composite material, comprising:
[0037] A composite material layer, the composite material layer comprising a filler and a core-shell structure thermal conductive material;
[0038] The filler is made of thermally conductive ceramic nanomaterial; the core-shell structure thermally conductive material comprises a core layer and a shell layer bonded to the core layer; the core layer is made of a material with a thermal conductivity greater than 10W / m·K, and the shell layer is made of thermally conductive ceramic nanomaterial;
[0039] A heat-conducting insulating layer is covered on the composite material layer; the heat-conducting insulating layer comprises a polymer material and a heat-conducting ceramic nano material.
[0040] Furthermore, the core layer material is selected from one of gold, silver, copper, aluminum and aluminum oxide.
[0041] Furthermore, the thermally conductive ceramic nanomaterial is selected from one or more of boron nitride, silicon nitride, titanium nitride, titanium dioxide, silicon carbide, aluminum nitride and gallium nitride.
[0042] Furthermore, the method for preparing the insulating ceramic layer includes:
[0043] Step 1) mixing the metal material as the core layer with the binder, then adding the cross-linking agent and the thermal conductive ceramic nanomaterial, and mixing them evenly to obtain the composite material layer coating;
[0044] Step 2) mixing the thermally conductive ceramic nanomaterial, the polymer, the cross-linking agent and the curing agent to obtain a thermally conductive insulating layer coating;
[0045] Step three) coating the composite material layer coating on the substrate, and forming a composite material layer after curing; coating the thermal conductive insulating layer coating on the surface of the composite material layer away from the substrate, and obtaining the thermal conductive composite material after curing.
[0046] Furthermore, the binder is selected from one of hydroxy silicone oil and curable epoxy.
[0047] Furthermore, the crosslinking agent is selected from one of diethylene glycol dimethacrylate, triallyl cyanurate, methyltrimethylsilane, cumene hydroperoxide, tetramethoxysiloxane and tetraethoxysilane.
[0048] Furthermore, the polymer resin is selected from one or more of polyvinyl alcohol resin, polyvinylidene fluoride resin, vinyl acetate, acrylic resin, polyurethane, epoxy resin, silicone resin, and phenolic resin.
[0049] Furthermore, the curing agent is selected from one of aliphatic amines, aromatic amines, alicyclic amines, polyamides, acid anhydrides, and tertiary amines.
[0050] Furthermore, in the step 1), 60-80 parts by volume of the metal material are mixed with 6-20 parts by volume of the binder, and the cross-linking agent and 20-40 parts by volume of the thermally conductive ceramic nanomaterial are mixed evenly to obtain a composite material layer coating; the amount of the cross-linking agent is 5-15% of the mass of the binder.
[0051] Furthermore, in the step 2), 10 parts by weight of thermally conductive ceramic nanomaterials, 20-80 parts by weight of polymers, 2-8 parts by weight of cross-linking agents and 5-20 parts by weight of curing agents are mixed to obtain a thermally conductive insulating layer coating.
[0052] The present invention also provides a vapor deposition cooling roller with an insulating ceramic layer on the surface, comprising a cooling metal roller and an insulating ceramic coating. The insulating ceramic coating is located on the outer surface of the cooling metal roller in contact with the film, and the insulating ceramic coating is prepared by the above ceramic layer method.
[0053] Furthermore, the thickness of the insulating ceramic coating is 30-200 μm.
[0054] The present invention also provides a method for preparing a composite current collector. The preparation method is based on the above-mentioned evaporation cooling roller with an insulating ceramic layer on the surface, and includes the following steps: applying the above-mentioned cooling metal roller coated with the insulating ceramic layer to the winding system of the vacuum evaporation chamber, and evaporating metal aluminum or copper on the PET or PP base film to form a composite current collector.
[0055] Furthermore, the composite current collector has a thickness of 3-13 μm.
[0056] Example 1
[0057] A method for preparing a vapor deposition cooling roller with an insulating ceramic layer on the surface, the specific steps are as follows:
[0058] (1) Preparation of aluminum / boron nitride core-shell structure thermal conductive material with a metal phase volume ratio of 70%:
[0059] 56.7 g of metal aluminum with a particle size of 30 μm and 2.9 g of hydroxy silicone oil were weighed and stirred, 0.29 g of tetraethoxysilane was added and mixed, and then 13.7 g of boron nitride with a particle size of 50 nm was added and mixed evenly to obtain a core-shell structure thermal conductive material.
[0060] (2) Preparation of filling materials with thermal conductivity and insulation properties:
[0061] Weigh 5 g of boron nitride thermal conductive ceramic nanomaterial with a particle size of 50 nm, 25 g of epoxy resin and 0.5 g of hydroxy silicone oil, and then add 5 g of low molecular weight polyamide curing agent and stir thoroughly to mix evenly.
[0062] (3) Preparation of a vapor deposition cooling roller with an insulating ceramic layer on the surface:
[0063] A layer of the core-shell structure thermal conductive material layer of step (1) with a thickness of about 50 um is first coated on the metal cooling roller, and the layer is left for 12 hours to solidify and form. Then, a layer of the filling material layer with thermal conductive and insulating properties of step (2) with a thickness of about 30 um is coated on the above core-shell structure thermal conductive material layer, and the layer is left overnight to solidify and form, thereby obtaining a vapor deposition cooling roller with an insulating ceramic layer on the surface.
[0064] Example 2
[0065] The difference from Example 1 is that step (1) is modified to weigh 48.6 g of metallic aluminum with a particle size of 30 μm and 2.9 g of hydroxy silicone oil, stir and mix, add 0.29 g of tetraethoxysilane and mix, then add 20.6 g of boron nitride with a particle size of 50 nm, and mix well to obtain a core-shell structure thermal conductive material.
[0066] Example 3
[0067] The difference from Example 1 is that step (1) is modified to weigh 188.2 g of metallic copper with a particle size of 30 μm, 2.9 g of hydroxy silicone oil, stir and mix, add 0.29 g of tetramethoxysiloxane and mix, then add 18.7 g of silicon nitride with a particle size of 50 nm, and mix well to obtain a core-shell structure thermal conductive material.
[0068] Example 4
[0069] The difference from Example 1 is that step (2) is modified to weigh 5 g of titanium dioxide thermal conductive ceramic nanomaterial with a particle size of 50 nm, 25 g of acrylic resin and 0.5 g of hydroxy silicone oil, mix them, and then add 5 g of low molecular weight polyamide curing agent and stir well to mix them evenly.
[0070] Embodiment 5:
[0071] This embodiment provides a method for preparing a composite current collector using a cooling metal roller coated with an insulating ceramic coating: the cooling metal roller coated with the insulating ceramic layer is applied to the winding system of a vacuum evaporation chamber, and metal aluminum is evaporated on a PET film to form a composite current collector.
[0072] Comparative Example 1: The difference from Example 1 is that in step (3), no material is coated on the cooling metal roller.
[0073] Comparative Example 2: The difference from Example 1 is that in step (3), only a layer of core-shell structure thermal conductive material layer with a thickness of about 50 um of step (1) is coated on the cooling metal roller, which is left to solidify for 12 hours without being coated with a filling material layer with thermal conductive insulating properties.
[0074] Comparative Example 3: The difference from Example 1 is that only a 30 um layer of the filling material with thermal insulation properties of step (2) is coated on the cooling metal roller, left overnight to solidify, and no shell-core structure thermal conductive material layer is coated.
[0075] Test example
[0076] The cooling rollers of Examples 1 to 4 and Comparative Examples 1 to 3 were used to prepare composite current collectors under the same preparation conditions using the method of Example 5, and the prepared composite current collectors were subjected to the following performance tests.
[0077] 1. The number of pinholes is measured by a defect detector: Cut a sample of 1×1m, place the sample on the detection surface of the defect detector, ensure that it is opaque on all sides, turn off the indoor lights, observe from a height of about 0.5m, and count the visible pinholes on the sample;
[0078] 2. The room temperature tensile strength of the composite aluminum foil is measured using an electronic universal material testing machine. The test conditions are: gauge length 10 mm, tensile speed 100 mm / min, width 15 mm. Other requirements are measured according to the method specified in GB / T 1040.3-2006.
[0079] 3. Film stripping times: Each sample was tested 10 times, and the number of times the base film fell off the roller was measured.
[0080] Table 1
[0081]
[0082]
[0083] If the thermal conductivity and cooling effect of the evaporation cooling roller is not good, when the aluminum liquid splashes to the film surface, it will cause thermal burns to the film surface, which will lead to the appearance of pinholes. As shown in Table 1, the present invention uses an evaporation cooling roller coated with a thermally conductive composite material, which has good thermal conductivity and can achieve rapid cooling of the base film. When the aluminum liquid splashes to the film surface, it can achieve rapid cooling, reduce the appearance of pinholes, and significantly improve the tensile strength. In addition, the dense ceramic coating on the cooling roller of the present invention has good thermal conductivity and good adhesion to the film, which increases the adhesion of the base film on the roller and reduces the risk of film stripping during evaporation.
[0084] Obviously, the above embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from them are still within the protection scope of the invention.
Claims
1. A thermally conductive composite material, characterized in that: include: A composite material layer, the composite material layer comprising a filler and a core-shell structure thermal conductive material; The filler is made of thermally conductive ceramic nanomaterial; The core-shell structure thermal conductive material comprises a core layer and a shell layer bonded to the core layer; The core layer is made of a material with a thermal conductivity greater than 10 W / m·K, and the shell layer is made of a thermally conductive ceramic nanomaterial; A heat-conducting insulating layer, the heat-conducting insulating layer covers the composite material layer; The thermally conductive insulating layer comprises a polymer material and a thermally conductive ceramic nano material.
2. The thermally conductive composite material according to claim 1, characterized in that: The core layer is selected from at least one of gold, silver, copper, aluminum, and aluminum oxide; Preferably, the core layer is spherical or irregularly spherical, and the average particle size of the core layer is 10-150 μm.
3. The thermally conductive composite material according to claim 1, characterized in that: The thermal conductivity of the thermally conductive ceramic nanomaterial in the composite material layer and the thermally conductive insulating layer is greater than 5 W / m·K; Preferably, the thermally conductive ceramic nanomaterials in the composite material layer and the thermally conductive insulating layer are independently selected from at least one of boron nitride, silicon nitride, titanium nitride, titanium dioxide, silicon carbide, aluminum nitride and gallium nitride.
4. The thermally conductive composite material according to claim 1, characterized in that: The average particle size of the thermally conductive ceramic nanomaterial is 20-500nm.
5. The thermally conductive composite material according to claim 1, characterized in that: The polymer material is selected from at least one of polyvinyl alcohol resin, polyvinylidene fluoride resin, vinyl acetate, acrylic resin, polyurethane, epoxy resin, silicone resin and phenolic resin.
6. The method for preparing the thermally conductive composite material according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: step 1) mixing a metal material as a core layer with a binder, then adding a cross-linking agent and a thermally conductive ceramic nanomaterial, and mixing them evenly to obtain a composite material layer coating; Step 2) mixing the thermally conductive ceramic nanomaterial, the polymer material, the cross-linking agent and the curing agent to obtain a thermally conductive insulating layer coating; Step 3) coating the composite material layer coating on the substrate and curing to form a composite material layer; A heat-conducting insulating layer coating is coated on the surface of the composite material layer away from the substrate, and the heat-conducting composite material is obtained after curing.
7. The method for preparing the thermally conductive composite material according to claim 6, characterized in that: The binder is selected from one of hydroxy silicone oil and curable epoxy resin; Preferably, the crosslinking agent is selected from one of diethylene glycol dimethacrylate, triallyl cyanurate, methyltrimethylsilane, cumene hydroperoxide, tetramethoxysiloxane and tetraethoxysilane; Preferably, the curing agent is selected from one of aliphatic amines, aromatic amines, alicyclic amines, polyamides, anhydrides, and tertiary amines; preferably, in the step 1), 60-80 parts by volume of the metal material are mixed with 6-20 parts by volume of the binder, and the cross-linking agent and 20-40 parts by volume of the thermally conductive ceramic nanomaterial are mixed uniformly to obtain a composite material layer coating; the amount of the cross-linking agent is 5-15% of the mass of the binder; Preferably, in step 2), 10 parts by weight of thermally conductive ceramic nanomaterial, 20-80 parts by weight of polymer, 2-8 parts by weight of cross-linking agent and 5-20 parts by weight of curing agent are mixed to obtain a thermally conductive insulating layer coating.
8. A cooling roller, characterized in that: It comprises a metal roller, on which is coated the thermally conductive composite material according to any one of claims 1 to 6; The composite material layer in the thermally conductive composite material is coated on the surface of the metal roller; The heat conductive insulating layer in the heat conductive composite material is disposed on a surface of the composite material layer away from the surface of the metal roller.
9. The cooling roller according to claim 8, characterized in that: The thickness of the thermally conductive composite material is 30-200 μm, wherein the thickness of the thermally conductive insulating layer is 10-100 μm, and the thickness of the composite material layer is 20-100 μm.
10. Use of the cooling roller according to claim 8 or 9 in preparing a composite current collector.
Citation Information
Patent Citations
Low-cost multifunctional high-efficiency polymer-based insulation and heat conduction composite material and preparation method thereof
CN105538647A
Multi-layer thermal-conductive composite material and preparation method thereof
CN108656676A
Cooling roll and method for producing thermoplastic resin sheet using same
CN110944821A
Core-shell spherical heat-conducting filler as well as preparation method and application thereof
CN112063020A
Cooling roller for vacuum PVD (Physical Vapor Deposition) coating equipment and preparation process of cooling roller
CN117107211A